Characteristics of opening in the ice cover formed by the gas vents - G. S. Bordonskiy; S. D. Krylov; A. A. Gurulev; A. O. Orlov; S. V. Tsyrenzhapov (Лëд и снег, 2018)
«Proparina» (russ) is a small hole in the ice cover formed by steaming of the ice by the gas vents. Some characteristics of this phenomenon were studied by the example of formation of one proparina found in March 2015 in the ice cover of the shallow eutrophic Lake Shakshinskoye (Trans-Baikal Region). The interest in this object is due to the fact that a proparina, unlike a polynya (small water opening in ice), is formed after the establishment of the ice cover and it can appear in those parts of a reservoir where there is no clearly expressed inflow or outflow of water. Although proparinas do often occur on some water bodies, e.g. Lake Baikal, a detailed description of their structure and process of formation is not available. Research on features of the proparina in the ice of the Lake Shakshinskoye and adjacent areas of this reservoir was carried out on March 25 and 28 in 2015. Melting at the lower and upper ice cover boundaries started at that time, and it was found that the proparina under investigation was formed in the center of a dome-shaped area where the ice thickness decreased compared to the adjoining parts within a distance of 200 meters. Gradient of the lower surface in the dome was on average 5 centimeters per 100 meters at a distance from the center. We found a narrow channel in the ice through which gas came into the proparina in the form of separate portions. The maximum recorded volume of gas that came into the open proparina reached 10 l/min. The channel is supposed to be formed at the end of winter period due to the release of gas during the melting of the lower layers of the ice cover and the subsequent movement of gas bubbles into the center of the dome. To study the ice cover structure, we measured thermo-microwave self-radiation of the “ice-water” system in the centimeter range. Such measurements allow detecting changes in ice thickness with an accuracy of 1 cm. It is assumed that the accumulation of gases under the ice causes the instability of the water column due to warming by the heat fl w from the bottom layers and initiates the circulation and, thus, formation of proparina.